CORRELAÇÃO ENTRE ÊRRO DE FECHAMENTO E ÊRRO DE ÃREA NOS LEVANTAMENTOS TOPOGRÃFICOS - Mello Netto, G. de; Godoy, R. (REVISTA DE AGRICULTURA, 2016)
CORRELAÇÃO ENTRE ÊRRO DE FECHAMENTO E ÊRRO DE ÃREA NOS LEVANTAMENTOS TOPOGRÃFICOS